Hubungan Dukungan Keluarga dan Dukungan Spritual dengan Kualitas Hidup Penderita Diabetes Mellitus di RSUD Kota Sabang - Riswanto Riswanto; Karmila Br Kaban; Alfando Tuju; Seprina Seprina; Tio Roganda Situmorang; Nur'aini Nur'aini (Universitas Malahayati Lampung, 2025)
ABSTRACT The high incidence of Diabetes Mellitus (DM) is inseparable from the many factors that influence it. In dealing with risk factors, knowledge is needed, which has a very important role in determining a person's attitude and behavior. In addition, family and spiritual support are no less important in improving the quality of life of people with DM. The purpose of this study was to determine the relationship between family support and spiritual support with the quality of life of patients with diabetes mellitus. The type of research used is an analytic descriptive survey with a Cross Sectional design. The population in this study were all patients with DM disease at Sabang City Hospital, totaling 168 people. The technique of taking subjects using simple random sampling as many as 63 people. The type of data used in this study is primary data. The instrument used in this study was a questionnaire to measure family support, spiritual support and quality of life of DM patients. The research data analysis was univariate and bivariate analysis with chi square test. The results of the study explained that there was a relationship between family support and the quality of life of DM patients with a p value = 0.0342 and there was a relationship between spiritual support and the quality of life of DM patients with p = 0.024. The conclusion of this study is that there is a relationship between family support and spiritual support with the quality of life of DM patients. It is recommended to encourage patients with DM to be active in relevant spiritual activities, such as prayer meetings, spiritual counseling, or religious communities Keywords: Family Support, Spiritual Support, Quality Of Life, Diabetes Mellitus ABSTRAK Tingginya angka kejadian Diabetes Mellitus (DM) tidak terlepas dari banyaknya faktor yang memengaruhinya. Dalam menangani faktor risiko dibutuhkan pengetahuan yang memiliki peran yang sangat penting dalam menentukan sikap dan perilaku seseorang. Selain itu, dukungan keluarga dan spritual juga tidak kalah penting dalam meningkatkan kualitas hidup penderita DM. Tujuan penelitian ini adalah untuk mengetahui hubungan dukungan keluarga dan dukungan spiritual dengan kualitas hidup penderita diabetes mellitus. Jenis penelitian yang digunakan adalah survei bersifat deskriptif analitik dengan rancangan Cross Sectional. Populasi dalam penelitian ini adalah seluruh pasien dengan penyakit DM di RSUD Kota Sabang sebanyak 168 orang. Teknik pengambilan subjek menggunakan simple random sampling sebanyak 63 orang. Instrumen yang digunakan dalam penelitian ini adalah kuesioner untuk mengukur dukungan keluarga, dukungan spiritual dan kualitas hidup pasien DM. Analisa data penelitian adalah analisis univariat dan bivariat dengan uji chi square. Hasil penelitian menjelaskan terdapat hubungan antara dukungan keluarga dengan kualitas hidup pasien DM dengan nilai p= 0,0342 dan terdapat hubungan dukungan spiritual dengan kualitas hidup pasien DM dengan p= 0,024. Kesimpulan penelitian ini adalah terdapat hubungan antara dukungan keluarga dan dukungan spiritual dengan kualitas hidup pasien DM. Disarankan untuk mendorong pasien DM untuk aktif dalam kegiatan spiritual yang relevan, seperti doa bersama, konseling spiritual, atau komunitas keagamaan Kata Kunci: Dukungan Keluarga, Dukungan Spiritual, Kualitas Hidup, Diabetes Mellitus